Effect of cyclic loading at elevated temperatures on the magnetic susceptibility of a magnetite-bearing ore. Issue 2 (5th October 2021) - Dudzisz, Katarzyna; Walter, Mario; Krumholz, Ralf; Reznik, Boris; Kontny, Agnes
SUMMARY: Cyclic loading at elevated temperatures occurs either naturally during tectonic or volcanic-induced earthquakes or can be human-induced due to various geological engineering activities. The aim of this study is to test if mechanical fatigue in rocks can be monitored by magnetic methods. For this purpose, the effect of cyclic-mechanical loading (150 ± 30 MPa) on the magnetic susceptibility and its anisotropy of a magnetite-bearing ore with varying temperatures (400 and 500 °C) and environment (air and vacuum) was investigated. Our study shows that magnetic susceptibility decreases significantly (up to 23 per cent) under air conditions and in vacuum (up to 4 per cent) within the first ca . 1000 cycles. Further loading does not significantly affect the magnetic susceptibility which then remains more or less constant. The decrease of susceptibility parameters is stronger at 500 °C compared to 400 °C under both experimental conditions. Magnetic susceptibility was always measured after decompression of the loaded sample at room temperature so that magnetostriction can be excluded as a reason for these changes. The higher the temperature at which samples were loaded the more pronounced is the oxidation of magnetite to haematite. The transformation of magnetite into haematite under ambient conditions is the most important mechanism influencing bulk magnetic properties. The weak changes in magnetic susceptibility after vacuum loadings are probably caused by intragranular microcracks formed on the surface of magnetite grains. These surface deformation structures are accompanied by the refinement of magnetic domains, which is observed by magnetic force microscopy. Bulk magnetic grain size modifications are also confirmed by hysteresis parameters as well as by the increasing Hopkinson peak ratios determined from magnetic susceptibility measurements over Curie point. The degree of magnetic anisotropy and shape factor only change for the air-treated samples and are therefore related to the haematite formation and not to irreversible ductile deformation in magnetite. Our experimental study shows that cyclic loading can change significantly the magnetic properties of a rock due to mineral transformation below < 1000 cycles and that the first stages of mechanical fatigue, which are a precursor of the failure of rock, are closely associated with these transformations.